Preparing for Group B Streptococcus vaccine. Attitudes of pregnant women in two countries. Issue 1 (31st December 2023) - Geoghegan, Sarah; Faerber, Jennifer; Stephens, Laura; Gillan, Hannah; Drew, Richard J.; Eogan, Maeve; Feemster, Kristen A.; Butler, Karina M.
ABSTRACT: Group B Streptococcus (GBS) vaccines, designed to be given to pregnant women, are in clinical trials. There is an opportunity to conduct preparatory research now to understand the drivers of and barriers to GBS vaccine acceptance. This will enable targeted interventions so that delays in vaccine uptake might be avoided. A multicenter, mixed-methodology, cross-sectional study evaluated the acceptability of a hypothetical GBS vaccine among pregnant women in two countries with differing health systems. Pregnant women in Philadelphia, US, and Dublin, Ireland, completed an electronic survey and a Discrete Choice Experiment. Five hundred and two women were included in the final analysis. Fifty-three percent of US and 30% of Irish participants reported both awareness and understanding of GBS. The median likelihood score for vaccine receipt (measured on a 10-point scale) was 9 (US: 9 (IQR 7–10), IRL: 9 (IQR 6–10)). Among the US participants, identifying as Black or African American was associated with a lower likelihood of vaccine receipt. Possession of a college degree was associated with increased likelihood of vaccine receipt. Perceived infant benefit was the most important driver of GBS vaccine acceptance. Safety concerns about a novel vaccine was the most prominent barrier identified. Good GBS vaccine uptake is achievable through strong messaging that highlights vaccine safety and the potential infant benefits. Preparation for vaccine implementation should include efforts to increase awareness among pregnant women about GBS infection and a continued focus on improving acceptability of currently recommended maternal vaccines, particularly in population subgroups with low uptake of maternal immunizations.